Archeologia dell'architettura religiosa e forme di potere all'Isola d'Elba tra XI e XII secolo - Ricci, Marta, (Limina/limites ;, 2022)
This study is a historical archaeological analysis of a territorial area including the Island of Elba, Monte Pisano and the neighboring plain, using the methodology of 'light' archeology: stratigraphic reading of the elevations and reading of the historical landscape.